Effects of Androgen Deprivation Therapy on Alzheimer's disease and Related Dementia Risk in the Million Veteran Program. (20th December 2022) - Panizzon, Matthew S.; Deka, Rishi; Anglin, Tori; Logue, Mark W.; Merritt, Victoria; Chang, Nai‐Chung N; Carter, Hannah K; Jasuja, Guneet; Lee, Kyung‐Min; Lynch, Julie; Pagadala, Meghana; Rose, Brenton; et al.
Abstract: Background: Androgen deprivation therapy (ADT) for prostate cancer depletes circulating testosterone levels and has been shown to increase risk for Alzheimer's disease (AD) and related dementias (ADRD). It is unclear whether ADT acts independently to increase ADRD risk, or whether effects of this treatment are exacerbated by the genetic risk for AD. We hypothesized that the effect of ADT on ADRD risk will be moderated by AD polygenic risk. Method: Clinical and genetic data were analyzed from 87, 060 United States Veterans, who had a diagnosis of prostate cancer and were participants in the Million Veterans Program (MVP) biorepository study. Clinical conditions, including diagnosis codes for ADRD, cancer, Charlson Comorbidity Index conditions, laboratory values (Gleason score, Prostate Specific Antigen levels), cancer treatments, and vital status were obtained from the Veterans Affairs (VA) longitudinal electronic health record data. A polygenic risk score (PRS) for AD was derived based on summary statistics from the Kunkle et al (2019) GWAS of Alzheimer's disease. The impact of ADT on ADRD was assessed using a time‐varying Fine‐Gray competing risks regression. Death from any cause was considered as a competing event to the development of ADRD. Result: There were 17, 092 (19.6%) patients who received ADT. 72% of the cohort was of white/European ancestry. The average age at prostate cancer diagnosis was 66 years. The median duration of ADT was 360 days. ADT users were more likely to be African American, and had higher PSA levels and Gleason Scores. ADT exposure and the AD PRS each showed significant main effects on ADRD risk, HRs = 1.16 (95% CI: 1.04 ; 1.29) and 1.10 (95% CI: 1.06 ; 1.15) respectively; however, we did not observe a significant interaction effect. Sensitivity analyses indicate that the association was not confounded by including Gleason score, PSA level, income, or education, and results were not altered significantly by excluding or focusing on the effect of the APOE :E4 locus. Conclusion: ADT significantly increases risk of ADRD, independent of underlying AD genetic risk factors. Further research is necessary in order to determine the mechanism by which androgen depletion contributes to the pathophysiology of ADRD.